A Novel Deoxyribonuclease Low-Molecular-Weight Bacteriocin, Carocin S4, from Pectobacterium carotovorum subsp. carotovorum - Wu, Huang-Pin; Derilo, Reymund C.; Hsu, Shih-Hao; Hu, Jia-Ming; Chuang, Duen-Yau (Microorganisms (Basel), 2023)
Pectobacterium carotovorum subsp. carotovorum (Pcc) is known to produce different types of bacteriocins, active protein substances that inhibit or kill related strains and are known to be induced by several factors. In this paper, we report the discovery, isolation, characterization, and functional analysis of Carocin S4, a novel low-molecular-weight bacteriocin (LMWB) from Pcc. A 2750 bp gene fragment was isolated from the chromosomal DNA of Pcc mutant strain rif-TO6, a rifampicin-resistant strain of TO6. The gene contains caroS4K and caroS4I within two open reading frames, which encode CaroS4K and CaroS4I, with molecular weights of about 90 kD and 10 kD, respectively. The unique characteristics of Carocin S4 were revealed after homology analysis with the previously discovered bacteriocins from Pcc. CaroS4K, which shares 23% and 85% homology with CaroS1K and CaroS3K, respectively, is also a deoxyribonuclease. However, unlike the two which can only hydrolyze genomic DNA, CaroS4K hydrolyzes both genomic and plasmid DNA. On the other hand, CaroS4K was found to be 90% homologous with CaroS2K but works differently in killing the target cell, as the latter is a ribonuclease. The optimal reaction temperature for CaroS4K to hydrolyze dsDNA is approximately 50 °C and requires the divalent metal ions Mg2+, Ca2+, and Zn2+ to catalyze its DNase activity. This study reveals another nuclease type of bacteriocin in Pcc, with CaroS4K and CaroS4I functioning as killer and immunity proteins, respectively.